The Tribe Scymnini (Coccinellidae: Coleoptera) From Sindh Province, Pakistan. Issue 1 (10th October 2015) - Ali, Muhammad; Perveen, Rukhsana; Naqvi, Arif-Un-Nisa; Ahmed, Khalil; Raza, Ghulam; Hussain, Ishtiaq
Abstract : Coccinellids are important natural enemies of aphids, scale insects, mealybugs, whiteflies, jassids and mites. They are being augmented or conserved for population reduction of different agricultural crop pests in the concept of Integrated Pest Management throughout the world. The genera and species in the tribe Scymnini known from Pakistan are revised and redescribed. Two genera including two subgenera and six species among which three species are newly reported, is therefore, a new addition to Coccinellid fauna of Pakistan. Keys to all taxa, descriptions of the higher taxa, species diagnoses, synonymies, and distribution records are included.